Perbedaan Perencanaan Pembelajaran PAI pada Kurikulum Merdeka di SMP dan SMA - Wahyuningsih, Sulistia; Sarwinda Roohmadani; Muhammad Sultan Al Viqri Rachman; Faelasup (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
The journal title you mentioned, "Differences in Islamic Religious Education (PAI) Learning Planning in the Independent Curriculum in Middle and High Schools," refers to research that compares Islamic Religious Education (PAI) learning planning strategies between Junior High School (SMP) and Senior High School (SMA) levels based on Independent Curriculum. This topic is very relevant in the educational context in Indonesia, especially with the adoption of the Independent Curriculum which emphasizes a more flexible and results-oriented learning approach. This journal can provide valuable insight for educational decision makers, curriculum developers, and PAI teachers to understand how the Merdeka Curriculum influences learning planning at the secondary school level.